Strengthening the Principle of Beneficence in Safeguarding Patient Data Confidentiality: An Analysis of the Roles and Responsibilities of Hospitals - Riyanto, Ontran Sumantri; Fuad (Fakultas Hukum Universitas Widya Mataram, 2025)
Confidentiality of patient data is a crucial aspect of healthcare services, supporting accurate medical decision-making and maintaining public trust. This study aims to analyze the role of hospitals in safeguarding patient data confidentiality through the application of the principle of beneficence. The research adopts a qualitative methodology with a descriptive approach, utilizing in-depth analysis to explore technical, legal, and ethical aspects of patient data management. Data collection techniques include interviews with medical personnel, observations of data management procedures, and reviews of data protection policies implemented by hospitals. This study examines strengthening hospitals' roles and responsibilities in protecting patient data confidentiality based on the principle of beneficence, as mandated by Law No. 17 of 2023 on Health. Hospitals are obligated to store and safeguard patient data at the highest standards, yet challenges arise with advancements in digital technology that increase the risk of data breaches. Additionally, medical personnel's lack of training in protecting patient data privacy poses another significant issue. Hospitals need to design clear internal policies and implement adequate security systems, such as encryption and access control. Further discussion highlights a beneficence-based model of responsibility, which prioritizes the patient’s best interests, including transparency in patient data management. Therefore, hospitals must enhance their data protection mechanisms by integrating the principle of beneficence to build patient trust and comply with legal obligations.